Ultrastable 2D material-wrapped copper nanowires for high-performance flexible and transparent energy devices - Kim, Jongyoun; Kim, Minkyoung; Jung, Hyeonwoo; Park, Jaehyoung; Lee, Youngu (Nano energy, 2023)
Wrapping metallic nanomaterials with two-dimensional (2D) materials can significantly improve the physical properties required for various electronic and catalytic applications. However, synthesizing 2D material-wrapped metal nanowires with highly organized shell morphology is still difficult because of their large surface area and high aspect ratio. We propose a simple and practical method for synthesizing 2D material-wrapped copper nanowires (CuNWs) with highly organized shell morphology by using 2D quantum dot (QD) assembly and flash light irradiation under low temperature and non-vacuum conditions. A uniform and thin layer of QDs comprising 2D material such as graphene or hexagonal boron nitride is constructed on the CuNW by using a solution process. The 2D QD-wrapped CuNW is then subjected to flash light irradiation to realize highly organized shell morphology. Microstructural observations showed that the flash light irradiation reconstructs the shell structure and improves crystal quality without structural deformation. The 2D material-wrapped CuNWs were used to fabricate transparent conducting electrodes (TCEs) exhibited outstanding oxidation stability, chemical stability, and mechanical durability. These TCEs were applied to realize high-performance transparent supercapacitors and heaters. In particular, the transparent supercapacitors based on the graphene-wrapped CuNW TCE demonstrated excellent capacitive behavior under acidic electrolyte conditions. They showed the highest areal capacitance (18.97 mF cm−2) compared to other metal nanowire-based transparent supercapacitors. Finally, a novel method for fabricating carbon and boron nitride nanotubes by wet-etching the core CuNW of the 2D material-wrapped CuNWs was successfully developed. [Display omitted] •2D material-wrapped copper nanowires were successfully synthesized.•TCEs based on the 2D material-wrapped CuNW exhibited outstanding stability.•Transparent supercapacitors based on the graphene-wrapped CuNW TCE showed the highest areal capacitance (18.97 mF cm−2).•2D material nanotubes were fabricated by wet-etching the core CuNW.